Für und wider die Einheitspsychose - Mundt, Christoph; Saß, Henning; Beer, Dagmar (Thieme, 1992)
Festschr. für Werner Janzarik
Beitr. teilw. engl., teilw. dt
Keywords: Janzarik, Werner -- 1920-2019; Konferenzschrift -- 1990 -- Schriesheim; Festschrift; Einheitspsychose